(untitled) (Doctor Virtualis, 2025)
Dedicating an issue of "Doctor Virtualis" to Critical Thought and the Middle Ages means for us, on the one hand, to reflect on the theoretical and historiographical bearing of the tradition to which we often refer, which intends to welcome and enliven the teaching of Mario Dal Pra from within, and on the other hand, to confront what critical thought has represented in a more general sense for European reflection As can be seen from the introductory pages and from the issue itself, the consideration of both levels, the ’local’ and the European, has led us to rethink the category of critical thought, questioning the appropriateness of its use in relation to an age before its actual formulation.